(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The subject of this study is the country’s accession to the World Trade Organization. The history of creation, goals and principles of functioning of the World Trade Organization (WTO) as an international institution were considered. The article analyzes the advantages and disadvantages of Uzbekistan’s accession to the WTO for the country’s economy.